Nicotinic Acid Regulates Glucose and Lipid Metabolism Through Lipidindependent Pathways - Liu, Dongwu; Wang, Xiaoqian; Kong, Ling; Chen, Zhiwei (Current Pharmaceutical Biotechnology, 2015)
Nicotinic acid (NA) decreases low density lipoprotein (LDL) cholesterol and increases highdensity lipoprotein (HDL) cholesterol at pharmacological doses 500-2000 mg/day, which further inhibits the progression of atherosclerosis and cardiovascular morbidity. However, some effects of NA may be mediated through lipid-independent pathways. NA participates in the regulation of glucose metabolism and the NAD-sirtuin pathway, which may relate to the altered mitochondrial biogenesis. NA exerts its anti-atherosclerotic or side effects via binding to GPR109A and receptor TRPV1. NA may regulate lipid metabolism via adipokines, especially TNFα and adiponectin. NA participates in several cellular pathways, including forkhead transcription factors, sirtuins, and protein kinase B. Though much progress on the regulatory effect of NA has been obtained, much remains to be determined about the exact cellular signal pathways on the regulatory mechanism. To reveal the mechanisms of excessive fatty deposition diseases, it is necessary to investigate the signaling pathways in the muscle, liver, and adipose tissue by which NA controls lipid metabolism. In this paper, we will review recent data on the pharmacological effects of NA and discuss how NA might be harnessed to regulate glucose and lipid metabolism through lipid-independent pathways.
Keywords: glucose metabolism